Metabolic Characterization of a Novel RORα Knockout Mouse Model without Ataxia - Billon, Cyrielle; Sitaula, Sadichha; Burris, Thomas P. (Frontiers in Endocrinology, 2017)
The retinoic acid receptor-related receptor α (RORα) is a nuclear receptor that plays an important role in regulation of metabolism and the immune system. Genetic models where the receptor is functionally deleted yield mice with significant cerebellar developmental issues associated with severe ataxia. Although many metabolic studies have been performed in these models, the impaired locomotor activity of these mice is known to affect their normal mobility and feeding behaviors. This creates some difficulty in interpretation of the role of RORα in models of metabolic disease where feeding and muscle function is a critical component of the pathophysiology. We generated a mouse with a floxed Rora allele that we crossed with a mouse line expressing Cre recombinase under the control of the EIIa promoter in order to obtain a full body deletion of Rora. This cross led to a partial deletion of the Rora locus likely due to mosaic expression of the EIIa-Cre transgene. These mice lack any signs of ataxia but display an improved metabolic profile relative to normal wt mice. The mice were resistant to diet- and age-induced metabolic syndrome and exhibited improved glucose tolerance and increased insulin sensitivity. Decreased RORα expression in the mice was also associated with reduced inflammation in models of metabolic syndrome. These data indicate that suppression of RORα activity improves metabolic function and reduces inflammation.